Transport protocol for real-time communication in Wireless Sensor Networks. (27th January 2010) - Stoina, Paul; Quintero, Alejandro; Cobo, Luis
Wireless sensors need data that arrive in time. This demand is fulfilled by a real-time communication for applications that use WSN technologies. The protocols, TCP and UDP, were not designed for real-time communication in wireless networks. The proposed protocol can manage data unit delays by considering time and space evaluations. The protocol designed in this study is compared with the UDP protocol. Both protocols are compared for the data units travel times and for the timelyput, which is the throughput of data units which arrive in time and which can be used by the application. This novel protocol achieves better results.